2018
DOI: 10.1080/23322039.2018.1443369
|View full text |Cite
|
Sign up to set email alerts
|

Testing capital structure theories using error correction models: Evidence from China, India, and South Africa

Abstract: The objective of this study is to empirically examine the capital structure theories that can explain the capital structure choice made by the firms that are operating in China, India, and South Africa. The study tests the capital structure theories as a stand-alone basis as well as an integrated framework of nested models using advanced dynamic panel data methods with a data-set of 1,183 firms with 12,187 firm-year observations spanning the period 1999-2016. Findings suggest that the firms adjust toward targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 58 publications
(133 reference statements)
5
19
0
Order By: Relevance
“…However, because of imperfections in the form of adjustment costs, there exists partial adjustment towards the target. The partial adjustment mechanism is based on the general framework explained by Flannery and Rangan (2006), Qian et al (2009), Cook and Tang (2010), McMillan and Camara (2012), Dang et al (2014), Zhou and Xie (2016) and Kannadhasan et al (2018) [Equation (2)]: …”
Section: Econometric Model and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…However, because of imperfections in the form of adjustment costs, there exists partial adjustment towards the target. The partial adjustment mechanism is based on the general framework explained by Flannery and Rangan (2006), Qian et al (2009), Cook and Tang (2010), McMillan and Camara (2012), Dang et al (2014), Zhou and Xie (2016) and Kannadhasan et al (2018) [Equation (2)]: …”
Section: Econometric Model and Methodologymentioning
confidence: 99%
“…System generalized method of moments (GMM) is deployed for the research (Blundell and Bond, 1998) because of the use of short panel data. It is suitable for a framework with endogenous explanatory variables and has the capability for securing consistent and efficient estimates in endogeneity issue[2] (Qian et al , 2009; De Jong, 2011; Dang et al , 2014; Ben-Nasr et al , 2015; Zhou et al , 2016; Belkhir et al , 2016; Kannadhasan et al , 2018).…”
Section: Econometric Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Flannery and Rangan (2006) and Nunkoo and Boateng (2010) observed that recent studies in developed countries have a tendency to use the GMM estimation technique to conduct empirical analyses on the capital structure issues. In addition, Kannadhasan et al (2018) emphasized that the GMM consistently estimates the dynamic model and deals with the endogenous problems by employing efficient instrumental variable (IV) techniques.…”
Section: Methodsmentioning
confidence: 99%